PENCITRAAN KEISLAMAN DALAM FILM AYAT-AYATCINTA - Hermawan, Herry (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2010)
This research  is concerned  with the social  construction   of islamic simbolization   reality  on films  and with the fac tors that constitute  this reality. Through the qualitative  research method,  the analysis  techniques  in use were genre and narrative  analysis,  and hermeneutics   analysis.Based  on research,  social  construction   of islamic  simbolization   reality  on film  is a reflection  of society  attitudeswhich  create  the polarization   have a cultural  context.  In this sense, film,  in the context  of social  construction   of reality,  is an arena  of ideas  and beliefs people   have  are systematically   related  to actual,  spiritual  and material conditions  of existence.The result of this research  showed  that islamic  simbolization   reality whether  it is constructed  by society  or by film derive from  the paramount realities  of interaction  between  religion  and culture.